A review on channel models in free space optical communication systems. (1st December 2017) - Anbarasi, K.; Hemanth, C.; Sangeetha, R.G.
Highlights: A survey on Free Space Optical communication is presented. Various channel models used in Free Space Optical communication are discussed. Mitigation techniques used in Free Space Optical communication are summarized. Performance analysis of relay and diversity techniques of various channels are tabulated. Abstract: Free Space Optical communication (FSO) is a wireless communication technology which uses light to transmit the data in free space. FSO has advantages like unlicensed spectrum and higher bandwidth. In this paper FSO system merits and demerits, challenges in FSO, and various channel models are discussed. To mitigate the turbulence in FSO the mitigation techniques like relaying, diversity schemes and adopting different modulation techniques used in different channels are discussed and its performance comparison is given.